2017
DOI: 10.1371/journal.pone.0189385
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of inflammatory breast cancer in patients with clinical inflammatory breast symptoms

Abstract: BackgroundTo describe a large cohort of women with non-puerperal inflammatory breast and to identify characteristics of inflammatory breast cancer.MethodsAll patients consulting for inflammatory breast syndrome in the breast unit of our tertiary University hospital between September 2013 and December 2015 were prospectively included. We excluded women who were pregnant or in the postpartum period. Patients underwent systematic clinical examination and imaging (breast ultrasonography and mammography). A biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In our study, a larger percentage of IBC cases reported a discrete mass, inverted nipple, warmth and pain, and a slightly smaller percentage reported itching compared to a U.S. study (24). However, the percentage of IBC cases reporting pain and skin thickening in our study was similar to that in a French study (16). Significant erythema of the skin was the most frequent initial symptom reported by cases in the U.S.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, a larger percentage of IBC cases reported a discrete mass, inverted nipple, warmth and pain, and a slightly smaller percentage reported itching compared to a U.S. study (24). However, the percentage of IBC cases reporting pain and skin thickening in our study was similar to that in a French study (16). Significant erythema of the skin was the most frequent initial symptom reported by cases in the U.S.…”
Section: Discussionsupporting
confidence: 75%
“…Here we describe the clinico-pathologic and mammographic characteristics of the IBC and non-IBC cases included in this study, expanding upon previous studies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). We also evaluate cases by photographic review and adherence to the two most recent definitions of IBC: the international expert panel consensus statement for standardized diagnosis (7) and the American Joint Committee on Cancer (AJCC) 8 th edition definition, which expands on the 7 th edition definition (which we used in our study) by considering duration history of symptoms/signs (2).…”
Section: Introductionmentioning
confidence: 89%
“…The criterium for histological diagnosis for IBC and IMC is the enormous neoplastic embolization of dermal lymphatic vessels which blockade lymphatic drainage originating the distinctive edema [4, 69]. The clinical form is characterized by a sudden presentation of erythema, firmness, warmth and pain resembling an inflammatory process and, therefore, this condition can be misdiagnosed with a dermatitis or mastitis, especially if a mammary nodule is absent [1, 2, 47]. Numerous epidemiologic, clinical and histopathological characteristics are shared by IBC and IMC, being the latter a good spontaneous animal model for the study of IBC [5, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…There can be ridges or indurations palpable within the skin, corresponding to the areas of lymphatic involvement, which are not contiguous. Ulceration or nodularity of the skin is less likely associated with IBC than with the more indolent LABC [9]. Whereas evidence of skin thickening is best seen with Magnetic Resonance (MR) imaging, conventional mammography and ultrasound can also detect this feature [10][11][12].…”
Section: Tablementioning
confidence: 99%